Understanding the utility of active learning by conducting science to teach science - Wilson, Abigail Rose (Kansas State University, 2018)
To retain students in science, technology, engineering, and mathematics (STEM) various pedagogical techniques, such as active learning, have been incorporated in STEM courses. Despite the popularity of active learning, it has rarely been empirically tested with a comparison or control group. To compare the benefits of active learning to conventional lecture learning, the aims of this project were twofold: conduct a physiological research project investigating thermoregulation in large ruminants and evaluate the effectiveness of active learning tools for an undergraduate course that focused on core concepts in physiology. Physiological concepts from the thermoregulation study were integrated into the educational portion of the study. Holstein heifers were used as the model organism for the thermoregulation study. Initially, 8 heifers were fitted with indwelling jugular catheters and serial blood samples were collected at 3-minute intervals during exercise of increasing intensity. Blood lactate was then measured and it was determined that the lactate threshold of Holstein heifers occurs on average at a heart rate of 145bpm ± 7.7 and at an exercise speed of 6.44km/h ± 0.3. The results from the lactate threshold test were used to design two 8-week exercise trials with the objective to examine the effects of exercise on heat stress using high-intensity (short bouts of exercise above the lactate threshold), low-intensity (relatively long bouts of exercise below the lactate threshold), and sedentary control treatments. No differences were found in weekly skin temperatures or core body temperatures (p >.05). Expression of lactate dehydrogenase A in skeletal muscle cells decreased in the high-intensity treatment (p =.03). Expression of lactate dehydrogenase B in skeletal muscles decreased in the high-intensity (p =.02) and sedentary control (p =.02) treatments. Skin and core body temperatures from all treatments were correlated with THI (p < 0.001). There were no differences in body weight, body condition score, or conception rate between treatments (p > .05). Although not significant (p > .05), after low-intensity exercise training, skin temperatures increased while core body temperatures decreased. Trends from this study warrant further investigation on the effects of low-intensity exercise on thermoregulation in Holstein cattle. The second component of this project involved the incorporation of core physiological concepts from the thermoregulation project, in conjunction with those identified by the American Physiological Society, into an educational study where the utility of active learning for teaching difficult concepts within an undergraduate physiology course was investigated. Using a design-based research approach, two distinct pedagogical tools were developed: an active learning tool in the form of a case study and a conventional lecture. It was hypothesized that, compared to a conventional lecture, students receiving the active learning tool would perform significantly better on tests measuring their ability to comprehend, apply, and transfer the information to novel scenarios. Results from this project did not support the hypothesis but instead led to the question of is it the method or is it the student? Prior knowledge of students was evaluated using a physiology knowledge assessment. Students with low prior knowledge had greater learning gains from the use of a conventional lecture while students with high prior knowledge had greater learning gains from the use of a case study. Students with fewer college credit hours completed and those with lower ACT scores had larger learning gains after receiving a conventional lecture compared to the use of a case study. Students with more college credit hours completed and those with higher ACT scores had larger learning gains from the use of a case study compared to receiving the information from a conventional lecture. Furthermore, students who relied on memorization for learning new information benefitted more from a conventional lecture, while students who relied on elaboration for learning new information benefitted more from a case study. Thus, the success of active learning likely depends on specific student characteristics. A one-size-fits-all approach to teaching and learning will not suffice; we must first consider the population of students and then select the proper instructional approach.
Keywords: Dairy cattle; Exercise and lactate threshold; Active learning; Conventional lecture learning; Case studiesHeat stress